Women Artists and Patrons in the Netherlands, 1500-1700 - Sutton, Elizabeth (Book collections on Project MUSE., 2019)
This essay collection features innovative scholarship on women artists and patrons in the Netherlands 1500-1700. Covering painting, printmaking, and patronage, authors highlight the contributions of women art makers in the Netherlands, showing that women were prominent as creators in their own time and deserve to be recognized as such today.